78‐4: IGZO‐based Identification Tags Communicating with Everyday Touchscreens. Issue 1 (25th September 2020) - Papadopoulos, Nikolaos; Celiker, Hikmet; Qiu, Weiming; Ameys, Marc; Smout, Steve; Willegems, Myriam; Deroo, Filip; van der Steen, Jan-Laurens; Kronemeijer, Auke Jisk; Dehouwer, Marco; Mityashin, Alexander; Gehlhaar, Robert; et al.
Abstract : In this work, we demonstrate a capacitive coupled data transfer with flexible thin‐film electronics using touchscreen as ubiquitous reader interface. The capacitive communication to the touchscreen is proven using a 64‐bit metal‐oxide thin‐film capacitive‐coupled identification tag. The tag is powered by a thin film battery or thin‐film photovoltaic cell that is converting the light of the screen. The thin‐film integrated tag has on‐chip monolithic electrodes (0.8cm 2 ), and the integrated circuit employs 409 transistors and dissipates only 140nW of power at 600mV supply voltage. The asynchronous data rate of the chip is up to 35bps, strictly limited by the touchscreen readout electronics.